Structural and Optical Properties of Spray Coated Carbon Hybrid Materials Applied to Transparent and Flexible Electrodes. (13th August 2017) - Wroblewski, Grzegorz; Swatowska, Barbara; Powroznik, Wieslaw; Jakubowska, Malgorzata; Stapinski, Tomasz
Abstract : Transparent and flexible electrodes were fabricated with cost-effective spray coating technique on polyethylene terephthalate foil substrates. Particularly designed paint compositions contained mixtures of multiwalled carbon nanotubes and graphene platelets to achieve their desired rheology and electrooptical layers parameters. Electrodes were prepared in standard technological conditions without the need of clean rooms or high temperature processing. The sheet resistance and optical transmittance of fabricated layers were tuned with the number of coatings; then the most suitable relation of these parameters was designated through the figure of merit. Optical measurements were performed in the range of wavelengths from 250 to 2500 nm with a spectrophotometer with the integration sphere. Spectral dependence of total and diffusive optical transmission for thin films with graphene platelet covered by multiwalled carbon nanotubes was designated which allowed determining the relative absorbance. Layer parameters such as thickness, refractive index, energy gap, and effective reflectance coefficient show the correlation of electrooptical properties with the technological conditions. Moreover the structural properties of fabricated layers were examined by means of the X-ray diffraction.